The Correlation between Women with Gestastional Hypertension and Preterm Birth Rates at Dr. Moewardi Hospital - Farrah Putri Amalia; Nutria Widya Purna Anggraini; Amandha Boy Timor Randita (Nexus Kedokteran Klinik, 2016)
Background: Hypertensive disorders of pregnancy is a medical problem that often arises in pregnant women. Hypertensive disorders of pregnancy contributes to various of perinatal outcomes, particularly preterm birth which is the most common cause of perinatal deaths. Gestational hypertension is one form of hypertensive disorders of pregnancy with the highest incidence rates. This study aims to determine the association between women with gestational hypertension and preterm birth rate at Dr. Moewardi Hospital. Methods: This research was an observational analytic study with cross sectional approach. The samples were pregnant women with gestational hypertension who gave birth at Dr. Moewardi Hospital in July 2014 - July 2015 (n = 87). The samples were selected by consecutive sampling method. Data of maternal blood pressure was obtained from medical records and grouped by the degree of hypertension (mild, moderate, severe). Data of gestational age of delivery was also obtained from medical records and divided into preterm (<37 weeks) and aterm (37 - 42 weeks) birth. Spearman test was used to measure correlation between variables with level of significance 5%. Results: There were a total of 35 preterm births of 87 mothers with gestational hypertension, with details as follows: 8 preterm births from mothers with mild hypertension (25.8%), 15 preterm births from mothers with moderate hypertension (60%), and 12 preterm births from mothers with severe hypertension (38.7%). Spearman correlation test showed a correlation coefficient (r) = -0.111 and p = 0.306. Conclusion: This research shows a statistically insignificant correlation (p=0.306) between women with gestational hypertension and preterm birth rate at Dr. Moewardi Hospital. Keywords: Gestational hypertension, preterm birth.